The heterogeneous employment outcomes of first- and second-generation immigrants in Belgium - Céline Piton; François Rycx (National Bank of Belgium, 2020)
This paper provides a comprehensive quantitative assessment of the relationship between people's migration background and their likelihood of being employed in Belgium. Using detailed quarterly data for the period 2008-2014, we find not only that first-generation immigrants face a substantial employment penalty (up to -36% points) vis-à-vis their native counterparts, but also that their descendants continue to face serious difficulties in accessing the labour market. The employment gap is, ceteris paribus, more pronounced for the first than for the second generation. Yet, intergenerational mobility patterns are found to be quite heterogeneous: although the children of immigrants from the European Union (EU) fare much better than their parents, the improvement is much more limited for those from EU candidate countries, and almost null for the second generation from the Maghreb. The situation of second-generation immigrants with only one foreign-born parent seems to be fairly good. In contrast, it appears that the social elevator is broken for descendants of two non-EU-born immigrants. Immigrant women are also found to be particularly affected, especially those originating from outside the EU. As regards education, it appears to be an important tool for fostering the labour market integration of descendants of non-EU-born immigrants. For firstgeneration immigrants, though, it proves to be much less effective overall. Focusing on the first generation, we find that: i) access to jobs increases with the duration of residence, though fairly slowly on average; ii) citizenship acquisition is associated with significantly better employment outcomes, for both EU and non-EU-born immigrants; iii) proficiency in the host country language is a key driver of access to employment, especially for non-EU-born immigrants; and iv) around a decade is needed for the employment gap between refugees and other foreign-born workers to be (largely) suppressed.
Keywords: J15; J16; J21; J24; J61; 330; First- and second-generation immigrants; employment; moderating factors